Consistency Indices in Analytic Hierarchy Process: A Review - Pant, Sangeeta; Kumar, Anuj; Ram, Mangey; Klochkov, Yury; Sharma, Hitesh Kumar (Mathematics (Basel), 2022)
A well-regarded as well as powerful method named the ‘analytic hierarchy process’ (AHP) uses mathematics and psychology for making and analysing complex decisions. This article aims to present a brief review of the consistency measure of the judgments in AHP. Judgments should not be random or illogical. Several researchers have developed different consistency measures to identify the rationality of judgments. This article summarises the consistency measures which have been proposed so far in the literature. Moreover, this paper describes briefly the functional relationships established in the literature among the well-known consistency indices. At last, some thoughtful research directions that can be helpful in further research to develop and improve the performance of AHP are provided as well.